Measurement and analysis of vibration characteristics of nanocrystalline magnetic core under symmetrical/asymmetrical waveforms - Chen, Bin; Xi, Binsheng; Wan, Nina; Wang, Shuaibing; Tang, Bo (Compel, 2023)
Purpose Because the nanocrystalline core is widely used in power electronic equipment, and the excitation waveform of its working mode is complex, the vibration at medium and high frequencies cannot be ignored. Therefore, this study aims to study the vibration mechanism of nanocrystalline strip and the vibration characteristics of nanocrystalline magnetic ring under different excitation waveforms. Design/methodology/approach First, the electromagnetic vibration mechanism between nanocrystalline strips is analyzed by finite element analysis, and the force of the magnetic ring with and without air gap is compared and analyzed. Then, the vibration of nanocrystalline magnetic ring under different excitation waveforms such as sine wave, triangular wave, symmetric rectangular wave and asymmetric rectangular wave is analyzed by experimental method. The acceleration time domain waveform measured by the experiment is analyzed by fast Fourier transform, and the vibration is analyzed according to the spectrum. Findings Because of the increase of magnetic flux leakage, the volume force density and the Maxwell force on the surface of the nanocrystalline magnetic ring will increase after the air gap is opened, resulting in the intensification of vibration. Under symmetric/asymmetric rectangular wave excitation, the vibration acceleration varies with the duty cycle. Due to the influence of harmonic excitation, the relationship between the main frequency of vibration and the excitation frequency is not two times, and its multiple decreases with the increase of excitation frequency. Originality/value The research and analysis of this paper can promote the application of new magnetic materials in electrical equipment in small and medium-sized and medium- to high-frequency fields.